"Vis-à-Vis Training" to Improve Emotional and Executive Competences in Very Preterm Children: A Pilot Study and Randomised Controlled Trial - Maria Chiara Liverani; Vanessa Siffredi; Greta Mikneviciute; Emma Mazza; Russia Ha-Vinh Leuchter; Petra Susan Hüppi; Cristina Borradori Tolsa; Edouard Gentaz (MDPI AG, 2024)
Background/Objectives: Premature birth can lead to socio-emotional, behavioural and executive problems that impact quality of life and school performance in the long term. The aim of this pilot study was to evaluate the feasibility and efficacy of a 12-week computerised training called Vis-à-vis to enhance these competencies in a cohort of very preterm (VPT) children aged 6 to 9. Methods: This pilot randomised controlled trial included 45 children born before 32 gestational weeks. Socio-emotional, behavioural and executive competencies were evaluated at three time points using computerised tasks, neuropsychological tests and questionnaires. Results: Among the eligible VPT children, 20% (n = 45) accepted to be part of the study, and 40% (n = 18) dropped out. Finally, 60% (n = 27) of the enrolled participants completed the study. Results showed a significant improvement in emotion knowledge and recognition immediately after the completion of the training. Conclusions: Overall, our results indicate that the implementation of this type of computerised training is feasible, but the overall compliance is unsatisfactory given the high dropout rate. Nevertheless, the positive effect of the training on emotion recognition encourages further exploration of these kinds of interventions to prevent adverse consequences in children born too soon.